The Urartian Bronze Collection at the University Museum: The Urartian Armor - Özgen, Engin
Diss.; director J. D. Muhly; Order No. 7919498 [human and horse armor, Urartian and Assyrian decorative motifs; cf. AJA 84 (1980) 123; Diss Abstr 40 (1979-80) 1571-A.